Essentials of Health Behavior: Social and Behavioral Theory in Public Health - Edberg, Mark (Burlington, MA : Jones & Bartlett Learning, 2020)
"Health promotion, education, and prevention programs ultimately focus on changing health behavior. Essentials of Health Behavior: Social and Behavioral Theory in Public Health, Third Edition provides the groundwork for understanding, assessing, and effectively applying theories of human behavior within the practice of public health. In clear and accessible language, this text provides the student with a background of the kinds of social and behavioral theories that guide our understanding of health related behavior and form the background for health promotion and prevention efforts. Filled with real life examples and profiles, the text explores some of the ways in which these theories and approaches are used in applied health promotion efforts. Key Features: Introduces students to the relationship between behavior and a selection of major health issues. Provides an introductory background to the kinds of social and behavioral theories that guide our understanding of health related behavior and form the background for health promotion and prevention efforts. Explores some of the ways in which these theories and approaches are used in applied health promotion efforts Since the publication of the second edition, health promotion theory has continued to evolve. The third edition keeps pace with developments such as rapidly evolving social media, increased global population diversity, and emerging epidemics, making the book useful and current. The Second Edition offers: Updates data and examples of application and practice throughout. Updated descriptions of selected theories to reflect more current distinctions in the constructs. New theoretical frameworks and expanded discussions of current theory such as the Integrated Model of Behavioral Prediction. An expanded discussion of the social norms construct. Additional material on social network theory. New discussion of Dissemination/Implementation research frameworks. New coverage of the evolution of Behavior Change Communications. Updated instructor ancillary materials. "--
Includes bibliographical references and index.
Keywords: Social medicine; Health behavior; Public health